Evaluation of Enoxaparin Dosing as a Risk Factor for Bleeding in Lung Transplant Recipients. (October 2016) - Sofjan, Amelia K.; Iuppa, Jennifer A.; Bain, K. Bennett; Deal, Eli N.; Witt, Chad A.; Hachem, Ramsey R.; Yusen, Roger D.
Background: Lung transplant recipients commonly develop complications that lead to anticoagulation. Standard FDA-approved enoxaparin dosing in this population results in a high incidence of above-goal anti-Xa levels, but its association with bleeding remains unclear.Objective: To evaluate the association between enoxaparin dosing and bleeding in lung transplant recipients and assess the relationship between dosing and anti-Xa levels.Methods: We conducted a single-center retrospective cohort study of adult lung transplant recipients who received therapeutic enoxaparin between 2000 and 2012 at a tertiary academic center. We dichotomized enoxaparin dosing regimens into standard dose (FDA-approved doses with a 10% rounding margin) and reduced dose. Clinicians ordered anti-Xa levels as deemed clinically appropriate. The primary outcome was major bleeding or clinically relevant nonmajor bleeding.Results: Of 222 patients treated with enoxaparin, 33 (14.9%) had bleeding events, of which half (17/33) were major. Bleeding occurred in 25/146 (17.1%) patients who received standard-dose enoxaparin versus 8/76 (10.5%) patients who received reduced-dose enoxaparin ( P = 0.190). Multiple logistic regression demonstrated an independent association between standard-dose enoxaparin and bleeding, after adjusting for confounders (adjusted odds ratio = 3.04; 95% CI = 1.14-8.10). The median enoxaparin dose in patients with above-goal versus at-goal anti-Xa levels was 0.89 versus 0.76 mg/kg every 12 hours; P = 0.006. However, doses yielding at-goal anti-Xa levels had an interquartile range of 0.67 to 0.90 mg/kg, which overlapped with doses yielding above- and below-goal anti-Xa levels.Conclusions: Enoxaparin dose reduction and anti-Xa level monitoring can improve drug safety and facilitate individualized dose optimization in lung transplant recipients.